Can they be compared? An essay on the historical development of welfare systems in Russia and Norway (Journal of Comparative Social Work, 2008)
This essay concentrates on the social modernization that took place in Russia and Norway during the period from the late 19th to the early 21st century by examining the origins and the subsequent development of their welfare systems, including the social legislation passed. The focus is on the professional assistance provided and the specialized workers engaged in social care for the underprivileged sections of the population.